Comparison of two different approaches of a class-A surface creation and quality verification. Issue 5 (3rd September 2018) - Gulanová, Jana; Lonek, Samo; Gulan, Ladislav
ABSTRACT: This paper focuses on specific description of a class-A surface creation, mostly used in the process of vehicle body development. Since there is a huge effort to modernize the procedure, two approaches of a class-A surface creation are compared. The first one is quite old and well known, and uses exclusively mathematical tools without any tree structure, hierarchy, or links. On the other hand, the second approach is closely linked to further procedure of components design using CAD tools. Both approaches are compared and broadly described using general objectives. Application of different procedures is demonstrated on a sport vehicle's body development and its class-A surface creation. GRAPHICAL ABSTRACT: